Analisis Perbandingan Beban Pajak Penghasilan Terhutang Menurut Pasal 31E Undang-Undang Pajak Penghasilan Dengan Peraturan Pemerintah Nomor 46 Tahun 2013 Pada PT ABC - P. Helen Widjaja; Jason Pratama (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
This case study was analyzed by comparing the income tax payable according to Article 31E of the Income Tax Law and Government Regulation No. 46 the Year 2013 on PT ABC. The results of this study prove that according to Government Regulation No. 46 the Year 2013 resulted in income tax payable is less than pursuant to Article 31e Income Tax Act